Ghostly Presence: An Abandoned Space and Three Religious Communities in Parishville, Quebec - Grigore Dovlete, Monica; Beaman, Lori (Eurostudia, 2017)
Once a religiously vibrant society, today Quebec is in the midst of a transition in its religious identity. Yet, the landscape of Quebec still preserves the marks of its perhaps more religious past. In other words, churches stand out in the contemporary panorama of the province. However, the lack of support by an active community has meant that many churches closed or face the threat of closure. Those religious groups that remain struggle to save their places of worship. The faithful of Parishville, both Catholic and Protestant, are no exception. This article explores the narratives of three religious groups (Anglican, United Church and Catholic) about an abandoned building that was once a church and then a Masonic Temple. Through our exploration of the aesthetic and material dimensions of the Masonic Temple we reveal aspects of the contemporary struggle of religious groups to survive as well as the fears, tensions and problems associated with this struggle. As it turns out, the Masonic Temple is a sort of ghostly presence, reminding the Protestant and Catholic parishioners of Parishville their own religious decline—the end of their building and the end of their faith.